STUDENTS’ PHONOLOGY IN READING ANECDOTE STORY FOR THE FIRST GRADE IN JUNIOR HIGH SCHOOL - NURMALIANA SARI; RANI RAKASIWI; MARIANI MERY ROSMIDA SILALAHI (JURNAL ILMIAH KOHESI, 2021)
This research focuses on phonology. The objective of this study is to dig student’s phonology in reading anecdote story for thefirst grade in junior high school. The research was conducted by using descriptive qualitative. There are two students takento read the anecdote story. Their voice is recorded and analyzed. It is found that the students’ phonology specially in readinganecdote story was both of them still lack in the word of countries [k ʌntris], wearing[w ærin], same [seim], clothes[kl ədz],difficult [di;fik əlt], whether[w əde;r], gentleman [dj əntlm ən], Washington [Wasin tən], tired[t ærd], down [daun].